The “Water” Imagery in Gu Cheng’s Group Poems “Mercury” 顾城《水银》组诗的“水”意象解读 - Hii, Eue Ee; Liau, Ping Leng (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2014)
Imagery has always been a bridge that establishes communication between human thoughts and objects around. In Gu Cheng’s poetry, he lets the imagery function by itself and act as the portrayal of their own essence. This paper intends to investigate the imagery in Gu Cheng’s group poems “Mercury”that reflects the proposition of “return to the origin/nature”. In Gu Cheng’s writing, the water archetypal image was selected not only because of the rich cultural heritage the water carried down, its chaos and formless nature which makes it possible to exist in variety forms, also show its suitability to represent the aspect of the origin world. Beyond that, Gu Cheng also related the language mode with the features of water to illustrate the fact that all things are the same in terms of essence, and demonstrates the method to return to the origin/ nature at the same time. When one’s self-consciousness disappears within the nature, one would have no place to turn to but to unite as one with the world. 意象长久以来扮演着沟通人与物之间的桥梁。在顾城的诗歌中，意象 更发挥了回归到本身及本质上的功用。本文旨在探讨顾城组诗《水银》里意象所 拼凑出来的有关“复归本源 / 自然”的命题。在顾城笔下，“水”这个承载了丰 富文化底蕴的原型意象，以无形与混沌的特质反映了世界本源的面貌。顾城更以 “水”意象来联系语言的状态，借此说明万物的本质是同一的，并展示了回归自 然的方法。当自我消失在自然之中，它没有别的去处，而是与万物合而为一。